Sustainability in environment and economics - Montemayor, Jose C. Jr. (Quezon City, Philippines : Central Book Supply, 2021)
This book therefore sets out the basics of sustainability, how they can possibly be attained and develop in an otherwise severely affected economy like he Philippines during covid times.
Sustainability in Environment and economics -- Circles of sustainability and the fourth dimension of sustainability -- Global Human -- Decoupling Environmental -- Sub-fields of sustainable -- Honing Goal Setting using -- General Action and in Action Goals -- Learning approach and learning avoidance -- Leadership and adaptive decision making -- Three processes model of future orientation -- Effect of parenting, siblings and peers.
Keywords: SUSTAINABLE DEVELOPMENT